Kinetic Analysis of Water Fitness Exercises: Contributions for Strength Development - Santos, Catarina (2020)
The evaluation of propulsive forces in water allows the selection of the most appropriate strategies to develop strength during water fitness sessions. The aim of this study was threefold: (i) to analyze the rate of force production; (ii) to analyze the rate of force variation; and (iii) to compare limbs' symmetry in two water fitness exercises. Twenty-two young health subjects (age: 21.23 ± 1.51 years old, body mass: 67.04 ± 9.31 kg, and height: 166.36 ± 8.01 cm) performed incremental protocols of horizontal adduction (HA) and rocking horse (RHadd), from 105 until 150 b·min-1. Data acquisition required an isokinetic dynamometer and a differential pressure system that allowed the assessment of (a) isometric peak force of dominant upper limb (IsometricFD); (b) propulsive peak force of dominant upper limb (PropulsiveFD); and (c) propulsive peak force of nondominant upper limb (PropulsiveFND). Significant differences were found in the rate of force production (RateFD) between the majority cadences in both exercises. The RateFD reached ~68% of the force in dry-land conditions, and lower cadences promoted a higher rate of force variation (ΔForce). Most actions were asymmetric, except for the HA at 135 b·min-1. In conclusion, the musical cadence of 135 b·min-1 seems to elicit a desired rate of force production with a symmetric motion in both exercises.